(untitled) - Zeng, Marcia Lei (New York, 2008)
In this new, authoritative textbook, internationally recognized metadata experts Zeng and Qin have created a comprehensive primer for advanced undergraduate, graduate, or continuing education courses in information organization, information technology, cataloging, digital libraries, electronic archives, and, of course, metadata. Instructors seeking a text that covers the theory as well as the how-to's of application design, implementation, and evaluation will find it here. An outcome-based approach lets learners with different orientations adapt their new knowledge and skills to any domain. Examples and practice problems focus on tasks typical to all metadata application projects. Other useful features include sample problems with solutions, quizzes, hands-on tutorials, and a recommended reading list at the end of each chapter. Individual modules can stand alone, for reference on an as-needed basis, when transitioning from traditional cataloging to compilations of metadata for locally created resources and Web sites, for example. Or you can study metadata systematically, module by module
Keywords: Metadata,Siêu dữ liệu